Aesthetic Transformation in Poetic Style Translations of The Qur’an - Wildan Taufiq; Edi Komarudin (ZAD Al-Mufassirin, 2026)
The shift in aesthetic values within Quranic poetry is investigated in this paper. Specifically, it analyzes two distinct works,  Muhamad Dipenogoro’s “Perkabaran” and H.B. Jassin’s “Bacaan Mulia”. The main issue addressed is the potential loss of Arabic literary value (balāghah) in prose translations of Qur’an into Indonesian. Using a comparative stylistic approach, this study analyzed Sūrat al-Fātiḥah and several chapters from the 30th juz of the Qur’an in “Bacaan Mulia” by H.B. Jassin and “Perkabaran” by Muhamad Dipenogoro. The analysis revealed that poetic translations partially preserved rhyme, rhythm, and diction. Another finding indicated that, in certain chapters, the translators successfully maintained the Arabic literary values (balāghah) equivalently in their translations, while in other parts, these values were not preserved to the same extent. However, they creatively produced aesthetically rich translations in sections where such literary aesthetics were not explicitly present in the original verses. Another important finding demonstrated that these poetic translations are not merely condensed renderings that convey meanings parallel to the original verses, but also communicate deeper interpretations and function as tafsīr-based translations. Thus, poetic translation represents a form of aesthetic interpretation of the Qur’an, which was originally revealed with a high degree of literary excellence.